Language learning: Human capital investment or consumption? - Matthias Huber; Silke Übelmesser (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2021)
This paper focuses on foreign language learning as human capital investment or consumption. We apply the human capital investment framework to foreign language learning and enlarge it by adding consumption motives. Based on a novel dataset collected from language course participants in 14 countries worldwide, we estimate individual and country-level determinants of the different motives for language learning and of the expected use of language skills in the labour market. We highlight possible spillovers from the consumption motive to professional use in the labour market, which emerge mostly in a "tied-mover" context. This provides guidance for targeted migration and integration policies.
Keywords: C82; E21; E22; F15; F22; 330; Language learning; new dataset; human capital investment; consumption